High numbers of tumor-infiltrating FOXP3-positive regulatory T cells are associated with improved overall survival in follicular lymphoma. - Carreras, J; Lopez-Guillermo, A; Fox, B; Colomo, L; Martinez, A; Roncador, G; Montserrat, E; Campo, E; Banham, A (2006)
The tumor microenvironment plays an important role in the biologic behavior of follicular lymphoma (FL), but the specific cell subsets involved in this regulation are unknown. To determine the impact of FOXP3-positive regulatory T cells (Tregs) in the progression and outcome of FL patients, we examined samples from 97 patients at diagnosis and 37 at first relapse with an anti-FOXP3 monoclonal antibody. Tregs were quantified using computerized image analysis. The median overall survival (OS) of the series was 9.9 years, and the FL International Prognostic Index (FLIPI) was prognostically significant. The median Treg percentage at diagnosis was 10.5%. Overall, 49 patients had more than 10% Tregs, 30 between 5% to 10%, and 19 less than 5%, with a 5-year OS of 80%, 74%, and 50%, respectively (P = .001). Patients with very low numbers of Tregs (< 5%) presented more frequently with refractory disease (P = .007). The prognostic significance of Treg numbers was independent of the FLIPI. Seven transformed diffuse large B-cell lymphomas (DLBCLs) had lower Treg percentages (mean: 3.3%) than FL grades 1,2 (mean: 12.1%) or 3 (mean: 9%) (P < .02). In conclusion, high Treg numbers predict improved survival of FL patients, while a marked reduction in Tregs is observed on transformation to DLBCL.